Pembinaan Kedisiplinan Belajar Siswa SMPN Kecamatan Makmur Kabupaten Bireuen - Saifuddin, Saifuddin (Tadabbur: Jurnal Peradaban Islam, 2022)
The purpose of this study was to determine the development of student learning discipline in SMPN Makmur, coaching discipline models of student learning in SMPN Makmur, and enabling and inhibiting factors in fostering student learning discipline in SMPN Makmur. This study is a field (field research) using qualitative methods. Collecting data in this study is done by observation, and interviews. Data analysis was performed by descriptive analysis through three stages: data reduction, data display and data verification. The results showed that the learning discipline enabling and inhibiting factors in fostering student learning discipline in SMPN Makmur is an attempt to direct the students to get used to comply with school rules. Fostering student learning discipline begins with planning, grouping, implementation, monitoring, evaluation, punishment, reward. Development of models of student learning discipline, namely: guidance, punishment, responsibility for actions, environmental modifications, and also made efforts to develop the discipline of students through extracurricular activities. In guiding the student discipline SMPN Makmur, there are several contributing factors and inhibitors, supporting factors are 1) The experience of a teacher, 2) Opt and obedience, 3) Facilities and infrastructure, 4) Awareness, 5) Willingness to discipline.